Advanced Recycling and Recovery of Spent Lithium-Ion Batteries with Bioleaching Processes using A. ferrooxidans to Achieve Cleaner Battery Production - Alhaqie, Ardika Dhafka; Dzahwan Mayvi Damay; Muhammad Tsaqif Haidar (Journal of Batteries for Renewable Energy and Electric Vehicles, 2023)
Nowadays, large amounts of Lithium-Ion Battery Waste (WLIB) are a serious problem. WLIB waste is hazardous and toxic waste. If special handling is not carried out, it will give a serious hazard to the environment and human health.  The project aims to extract WLIB in the form of Li2CO3 electrodes, which will then be recovered using a bioleaching process using A. ferrooxidans as biological agent to achieve improved Life Cycle Assessment of battery production. By cultivating the bacteria at a low pH, maximized through the use of strong acids, metal catalyst, the metal waste can be dissolved into ions. These ions can then be chemically consolidated and transformed into new battery electrodes. Subsequently, the material was subjected to chemical and electrochemical testing using cyclic voltammetry (CV) at a scan rate of 0.1 mV/s and charge-discharge (CD) measurements at a scan rate of 0.1 C. Effect of catalysis at bioleaching process using A.ferooxidans is dissolve 99.9% cobalt and gives 94% efficiency at S/L ratio of 6. The purity of Li2CO3 produced by bioleaching is higher than commercial Li2CO3.  Electrochemical tests show that recycled Li2CO3 has initial capacity respectively of 102 mAh/g and capacity retention of 79% after 50 cycles at 1C while commercial percussors lower. WLIB recycling using bioleaching processes could produce weak organic acid waste, more environmentally friendly than the cathode synthesis process from metal precursors (commercial Li2CO3). This innovation is interesting to develop because it will produce batteries that are cleaner and more efficient than commercial battery products.